A study of metonymical and metaphorical shift of meaning In selected examples - Ali Ghan (آداب الكوفة, 2013)
It has been seen that a language may gain or lose lexical items . Additionally , the meaning or the semantic representation of words may change, by becoming broader or narrower, or by shifting. A lexical item may undergo a shift in meaning . For example, the word knight once meant 'youth' but shifted to 'mounted man  -at- arms'. Silly used to mean 'happy' in old English. By the middle English period it shifted to mean ''naïve'', and only in modern English does it mean 'foolish'. The present study tries to identify the main differences between the metonymical and metaphorical shift of meanings used in the selected examples. It is hypothesized that both metonymy and metaphor are figures of speech; the former works by contiguity(association) between two concepts, while the latter works by the similarity between them. The steps to be followed in this study are exploring semantic change , identifying  its types and investigating the metonymical and metaphorical shift of meanings, showing their differences and correlation used in the selected examples. The analysis of the data has shown that metaphor and metonymy, though quite different in their mechanism, may work together seamlessly. A metaphor produces a new concept in the target domain, a concept that is similar to the origin concept of the source domain because it contains certain elements of the source concept. Metonymy is quite different from metaphor- when talking metonymically, the same domain is remained. An element from the original concept  is borrowed, but the links to the other elements are remained. The relations between the general objects and the things or aspects belonging to it are only possible within one domain. A metonymical shifts shift the reference of the word from a standard referent to an essential element of the underlying concept. Finally, it is necessary to observe that metonymy and metaphor are not mutually exclusive, but rather complemented one another . They are interacted in practice to achieve and enhance cohesion and coherence of the utterances.